PERLINDUNGAN HUKUM NASABAH ASURANSI YANG MENOLAK RESTRUKTURISASI POLIS PADA PERUSAHAAN ASURANSI YANG MENGALAMI GAGAL BAYAR (STUDI KASUS PADA PT ASURANSI JIWASRAYA (PERSERO) - Widhiantara, Anggara Pradnya; Indiraharti, Novina Sri (Fakultas Hukum Universitas Trisakti, 2023)
The financial problem of PT Asuransi Jiwasraya (Persero) made the company unable to pay the insurance policy holders’ claim. However, even though the company had offered an option for its policy holders to restructure their policy, there are policy holders who refused that option, and instead sued the company and demanded immediate payment. This research tries to highlight the form of legal protection in the insurance policy and judges’ considerations which are given to policy holders who refused the restructurization option. From the results of the analysis, it was concluded that the legal protection had been provided in the insurance policy, in the form of dispute resolution mechanisms provided, which are able to be chosen by the policy holders. Furthermore, in the judges’ considerations on the cases which are the objects of the research, it was concluded that the judges had attempted to provide legal protection, however the protection wasn’t perfect, because there are potential errors in the legal rules used as the basis for the considerations. For this reason, this research suggests that judicial institutions should be more cautious in giving legal protection, so that the rights of all policy holders can be protected.